A Critical Analysis of Methodology Pitfalls in Duplex Doppler Ultrasound in the Evaluation of Patients with Erectile Dysfunction: Technical and Interpretation Deficiencies. Issue 8 (3rd July 2020) - Nascimento, Bruno; Miranda, Eduardo P.; Terrier, Jean-Etienne; Carneiro, Felipe; Mulhall, John P.
Abstract: Background: Penile duplex Doppler ultrasound (PDDU) is a minimally invasive tool to evaluate erectile hemodynamics in patients with erectile dysfunction (ED). Despite decades of use, there is still a large variability in PDDU protocols, and a high rate of false diagnosis is reported. Aim: Review of PDDU methodology in the published literature addressing protocol heterogeneity, technical and interpretation challenges. Methods: A PubMed literature search was performed using the search terms "penile doppler ultrasound", "penile duplex ultrasound" or "penile ultrasound", and "Erectile dysfunction". Studies were analyzed for the presence of the following elements in reporting of the PDDU protocol: (i) intracavernosal vasoactive agents used, (ii) use of a redosing protocol, (iii) means of rigidity assessment, (iv) report of at-home best-quality erection, (v) normative criteria for peak systolic velocity (PSV) and end-diastolic velocity (EDV), and (vi) use of time-based hemodynamics assessment. Inclusion criteria were studies available in English, from 2005 onwards, and with full text. Exclusion criteria were review, descriptive or short communication articles, animal studies, and studies in populations other than those with ED. Outcomes: A critical review of the heterogeneity in published literature was performed to guide a structured discussion of methodological challenges and to create a list of recommendations. Results: Significant heterogeneity was seen in key methodological aspects. Fifty percent of studies reported the use of prostaglandin E1 only, and 12% of studies did not mention the agent used. Redosing as part of the PDDU protocol was mentioned in only 26% of studies. The majority (56%) did not mention any form of rigidity assessment. The most frequently used grading system was the Erection Hardness Score (14%). Overall, most studies (59%) used a timed-base protocol for hemodynamic assessment. No clear consensus was defined for normative criteria for PSV and EDV, 39% defining a normal PSV as ≥30 cm/s, and 57% using EDV values ≤5 cm/sec as normal. Clinical Implications: The absence of standardization has led to inadequate reporting of key factors which has rendered data interpretation and comparison between studies challenging. Strengths and Limitations: Our strengths include an extensive review of literature, with a structured analysis of the impact of each methodological pitfall. Our main limitation is the fact that protocol reporting, and not its application, was assessed. Conclusion: Despite its widespread use, analysis of the literature on PDDU use in the ED population shows marked protocol heterogeneity, rendering data interpretation a problem.